Self-Regulated Learning (SRL): A guide for the perplexed. (3rd July 2019) - Zeidner, Moshe; Stoeger, Heidrun
ABSTRACT: This introductory paper to the special issue of High Ability Studies aims to provide a "guide for the perplexed" relating to self-regulated learning (SRL) theory, research, and applications. We begin by defining SRL and its key cyclical stages and criterial attributes. We move on to discuss a number of motivational and meta-motivational constructs supporting SRL. We then briefly present a number of issues related to teaching and promoting SRL. Finally, we review research shedding light on SRL in gifted, high ability, and high achieving students.